The murders of the messengers: Stephen versus Zechariah and the ethical values "New" versus "Old" Testament - Kalimi, Isaac (Australian biblical review, 2008)
In Chronicles and Acts an analogous story is narrated about the martyrdom of two divine messengers: Zechariah (2 Chr 24:20-22) and Stephen (Acts 6:8-7:60). This article suggests that the author of Luke-Acts based his story of Stephen in contrast to that of the Chronicler in order to stress the claim to greater ethical merit of "love and forgiveness" of the new religion in contrast to the incompatible vengeance of the old religion.